Business intelligence: a key tool for the use of information and business decision-making (Revista de Investigaciones Universidad del Quindío, 2021)
In the current environment where small and medium-sized companies develop, it has changed as a result of the commercial opening that took place after the Second World War. The objective of this article is to analyze the importance of applying Business Intelligence as a key tool for small and medium-sized companies to use information as an input to support business decision-making. The methodology used is through a document review with a tool, with a descriptive qualitative approach. Scientific databases such as Dialnet, ScienceDirect and Scielo and keywords such as Business intelligence, Decision making, Information were used to carry out a theoretical, critical and comparative analysis of the contributions of the Business Intelligence authors. The results indicate that Business Intelligence has the components of an interactive process, explore, analyze, data warehouse, technology and communicate. It is concluded that Business Intelligence is a valuable and viable solution for organizations because through its use and application they provide decision makers with the facility to make decisions supported by knowledge.
Keywords: Business intelligence; information; decision making